Psychometric Properties and Rasch Validation of the Teachers’ Version of the Perception of Resources Questionnaire - Alnahdi, Ghaleb H.; Goldan, Janka; Schwab, Susanne (Frontiers in Psychology, 2021)
Research indicates that the perception of available resources is a key factor for the implementation of inclusive education. Regarding the teachers, a relatively high level of perceived personnel and physical resources is associated with more positive attitudes toward inclusive education and experiencing a higher level of self-efficacy. Thus, this study aims to examine the psychometric properties of the teacher version of the Perceptions of Resources Questionnaire (PRQ-T). Data were collected from a sample of 1,078 in-service teachers in Austria. Different statistical analyses were used, including Rasch analysis and confirmatory factor analysis. The results indicated good psychometric properties of the PRQ-T regarding internal consistency measured by person separation index (PSI) and construct validity by both confirmatory factor analysis and the Rasch analysis. Moreover, the findings supported that the PRQ-T is a two-factor scale to measure teachers’ perceptions of personnel and physical resources in inclusive education. Further studies with different samples are necessary to confirm the findings.